How do Risk Perceptions Respond to Information? The Case of Radon - Smith, V. Kerry; Johnson, F. Reed (The Review of Economics and Statistics, 1988)
A specialized survey of Maine households' responses to information about the risks associate d with radon concentrations in their homes and water supplies was use d to evaluate how they form risk perceptions. The findings support a modified form of a Bayesian learning model to describe how individual s used the information to revise their risk perceptions. Moreover, in dividuals who took some mitigating actions reported lower risk percep tions after that action. The overall results are potentially importan t to the use of information programs as policy instruments for risk r eduction because they indicate that new information can affect risk p erceptions in a systematic way. Copyright 1988 by MIT Press.